2017
DOI: 10.3390/ijgi6050151
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Behavior Analysis and Pheromone-Based Fusion Model for Big Trace Data

Abstract: People leave traces of movements that might affect the behavior of others both online in cyberspace and offline in real space. Previous studies, however, have used only questionnaires, network data, or GPS data to study spatio-temporal behaviors, ignoring the relationship between online and offline activities, and overlooking the influence of previous activities on future behaviors. We propose a Pheromone-based Fusion Model, viewing human behaviors as similar to insect foraging behaviors to model spatio-tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the Graph Theory, the complex network of GPS trajectories is composed of many trajectory points with GPS coordinates and segments. Those coordinates and trajectory segments involve much information of human mobility patterns, such as the range of travel, the interest locations and paths, the critical locations and paths, the optimal paths, and the transportation modes 14–16 . The GPS trajectory complex network can assist to interpret the intersections and distributions of trajectories.…”
Section: Proposed Paradigmmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Graph Theory, the complex network of GPS trajectories is composed of many trajectory points with GPS coordinates and segments. Those coordinates and trajectory segments involve much information of human mobility patterns, such as the range of travel, the interest locations and paths, the critical locations and paths, the optimal paths, and the transportation modes 14–16 . The GPS trajectory complex network can assist to interpret the intersections and distributions of trajectories.…”
Section: Proposed Paradigmmentioning
confidence: 99%
“…Those coordinates and trajectory segments involve much information of human mobility patterns, such as the range of travel, the interest locations and paths, the critical locations and paths, the optimal paths, and the transportation modes. [14][15][16] The GPS trajectory complex network can assist to interpret the intersections and distributions of trajectories. Moreover, several network analysis metrics, such as the degree centrality, Betweenness, Closeness, and shortest path, can be employed to mine the human mobility patterns.…”
Section: Proposed Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Urban vitality research is facing the transformation of the research paradigm and the innovation of data and methods. The rapid development and popularity of wireless communication, mobile positioning, and Internet technologies make it possible to obtain human behavior and activity patterns based on massive spatio-temporal trajectories at individual granularity [19,20]. Mobile phone signaling data [21], GPS trajectory [22], social media data [23], etc., have been gradually applied by scholars in the study of urban vitality measurement.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of information and communication technologies (ICT), massive amounts of crowdsourced data (e.g., mobile phone record data, taxi trajectory data and social media check-in data) are well captured. These data are plentiful and accessible, and they contain a wealth of information about human activities and socioeconomics, providing strong support for understanding urban land use [38][39][40]. Reades et al [41] analyzed the relationship between mobile phone data and business land and identified different mobile phone usage patterns between business and residential land.…”
Section: Introductionmentioning
confidence: 99%